2020
DOI: 10.3233/jpd-201978
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Time to Discontinuation of Levodopa-Carbidopa Intestinal Gel Infusion: A Retrospective Cohort Study

Abstract: Background: Continuous intra-duodenal infusion of levodopa-carbidopa intestinal gel (LCIG) is a well-established therapy for patients with advanced Parkinson's disease (PD) suffering from motor complications despite optimized treatment with oral dopaminomimetics. However, time to discontinuation of treatment with LCIG varies considerably between patients, ranging from a few months to more than ten years. To improve the selection of candidates for LCIG, knowledge of prognostic factors is of paramount importance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 36 publications
2
17
1
Order By: Relevance
“…[7][8][9][10][11] However, there are relatively few studies considering longterm features of the LCIG treatment. [12][13][14][15][16][17] Studies have found an average duration of 7 to 8 years of LCIG infusion 13,14 and a high…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11] However, there are relatively few studies considering longterm features of the LCIG treatment. [12][13][14][15][16][17] Studies have found an average duration of 7 to 8 years of LCIG infusion 13,14 and a high…”
mentioning
confidence: 99%
“…18,19 Some authors have reported a group of patients who discontinue the treatment early on. 13,20,21 Others have found somewhat conflicting risk-factors for discontinuation such as longer 14 or shorter 13 duration of PD before initiation of the infusion and female gender. 14,16 Here, we report single-center findings including changes in medication, treatment duration, and adverse events of patients treated with the LCIG-infusion based on data analysis of 103 consecutive PD patients treated with LCIG at Helsinki University Hospital between July 2006 and May 2020.…”
mentioning
confidence: 99%
“…However, a retrospective examination of medical records for patients receiving CSAI for at least 6 months found that the most common reason for discontinuation was troublesome dyskinesia, and many younger patients transitioned to DBS following CSAI therapy [27]. A recent retrospective analysis of patients who received LCIG for an average of 2.6 years found that the most common reasons for discontinuation were device-related side effects and less efficacy than expected by the patient [28]. In another retrospective study, the discontinuation rate was 21% during an average of 22 months of LCIG treatment, with death and poor compliance being the primary reasons; device-related complications and complications with percutaneous endoscopic gastrojejunostomy occurred, but did not lead to the discontinuation of LCIG [29].…”
Section: Discussionmentioning
confidence: 99%
“…There are as of yet no standardized protocols guiding the timing of tube replacements, which could potentially aid in preventing PEG-J-related complications in an already fragile population. Device complications are a known cause of LICG discontinuation [ 12 ] and avoiding them could help prolong effective treatment in certain patients.…”
Section: Discussionmentioning
confidence: 99%